The Role of School Principals' Leadership in Supporting Learning Media Innovation in Early Childhood Education: A Literature Review - Risnajayanti Risnajayanti; Nurlina Nurlina; Waode Sari Amalia; Nurul Idhayani; Sitti Salma; Hadijah Selman (CV. Ulil Albab Corp, 2026)
The leadership of school principals has a strategic role in supporting learning media innovation in Early Childhood Education (ECE). However, the results of research on this role are still scattered in various publications, so a study is needed that can provide a comprehensive picture. This study aims to analyze the role of school principal leadership in supporting learning media innovation in ECE through a literature review. Research data sources were obtained from scientific articles searched on Scopus, ScienceDirect, and Google Scholar databases using keywords relevant to the research topic. Based on the selection criteria that have been set, 16 articles were obtained that were analyzed using content analysis techniques through thematic grouping, identification of finding patterns, and synthesis of research results. The results of the study show that the leadership of school principals supports learning media innovation through four main roles, namely building an innovation-oriented school vision and culture, developing teacher competencies in a sustainable manner, encouraging the use of digital technology in learning, and carrying out academic supervision and collaboration with various parties. Thus, the leadership of school principals that is adaptive, collaborative, and learning-oriented is an important factor in supporting learning media innovation in ECE.